2016
DOI: 10.1093/jnci/djw132
|View full text |Cite
|
Sign up to set email alerts
|

Eradication ofHelicobacter pyloriand Gastric Cancer: A Systematic Review and Meta-analysis of Cohort Studies

Abstract: This systematic review and meta-analysis indicates that eradication therapy for H. pylori prevents gastric cancer. There was insufficient literature for meta-analysis of MALT lymphoma or esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
68
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 57 publications
2
68
0
1
Order By: Relevance
“…Moreover, the risk of gastric cancer in H. pylori -uninfected subjects is extremely low in Japan [24]. Thus, the purpose of gastric cancer screening using serum test is to detect strictly H. pylori -infected subjects and H. pylori post-eradication subjects because eradiation merely reduces the incidence of gastric cancer to 54% [27]. In this study, 18 of 33 (54.5%) post-eradication subjects were classified into Group C using the ABC method before eradication, suggesting that they were originally a relatively high-risk group, and periodic endoscopic surveillance should be performed even after eradication.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the risk of gastric cancer in H. pylori -uninfected subjects is extremely low in Japan [24]. Thus, the purpose of gastric cancer screening using serum test is to detect strictly H. pylori -infected subjects and H. pylori post-eradication subjects because eradiation merely reduces the incidence of gastric cancer to 54% [27]. In this study, 18 of 33 (54.5%) post-eradication subjects were classified into Group C using the ABC method before eradication, suggesting that they were originally a relatively high-risk group, and periodic endoscopic surveillance should be performed even after eradication.…”
Section: Discussionmentioning
confidence: 99%
“…5 Systematic reviews and meta-analyses have demonstrated that the eradication of H. pylori can effectively reduce the incidence of GC by 34%-54%. 6,7 Other studies have found that eradication of H. pylori can partially reverse gastric atrophy but cannot reverse intestinal metaplasia. 8,9 Therefore, the eradication of H. pylori cannot completely prevent the occurrence of GC.…”
mentioning
confidence: 99%
“…In addition, these results need to be validated in other ethnic groups. Although the eradication of H. pylori reduces gastric cancer risk, the risk reduction is as low as 30%‐40%, and a substantial proportion of the subjects develop gastric cancer even after H. pylori eradiation . Because post‐eradication gastric cancer is an important clinical problem, the development of a risk‐prediction system is necessary to identify high‐risk individuals with current or past H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the eradication of H. pylori reduces gastric cancer risk, the risk reduction is as low as 30%-40%, and a substantial proportion of the subjects develop gastric cancer even after H. pylori eradiation. 55 Because post-eradication gastric cancer is an important clinical problem, the development of a riskprediction system is necessary to identify high-risk individuals with current or past H. pylori infection. We hope our findings will contribute to the elucidation of the molecular pathology of gastric cancer and the implementation of personalized medical care for this disease.…”
Section: Discussionmentioning
confidence: 99%